Limitation of photosynthetic carbon metabolism in South African soybean genotypes in response to low night temperatures / Abram Johannes Strauss - Strauss, Abram Johannes (North-West University, 2011)
Thesis (Ph.D. (Botany))--North-West University, Potchefstroom Campus, 2009.